Comparison of Various Techniques for Left Ventricular Ejection Fraction - Asad Khan, Farhat Shireen, Auqib Ghulam Shah, Imran Mehboob Baig, Muhammad Abdul Mateen, Muhammad Shahid (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to compare the sufficient accuracy of three different techniques of echocardiography for left ventricular ejection fraction. Study Design: Retrospective study Place and Duration: Saidu Group Of Teaching Hospital, Saidu Sharif, Swat, KPK, From September, 2021 to February, 2022. Methods: Total 90 patients of both genders with age 18-70 years were included. All the patients admitted to hospital with complaint of chest pain. After getting informed written consent detailed demographics of enrolled cases were recorded. All of these techniques (M-mode echocardiography, simpson’s biplane mode and global longitudinal strain) were used to measure the left ventricular ejection fraction of patients within a 3-month period that did not include a myocardial infarction or revascularization. SPSS 23.0 was used to analyze all data. Results: We found that 82 (91.1%) were male patients and 8 (8.9%) were females. Mean age of the patients was 53.6±12.47 years and had mean BMI 25.8±11.44 kg/m2. Hypertension was found in 50 (55.6%) cases, followed by dyslipidemia in 35 (38.9%) patients, diabetes mellitus in 23 (25.6%) cases. Cigarette smokers were 15 (16.7%). We found that accuracy of global longitudinal strain was higher for left ventricular ejection fraction than that M-mode echocardiography and simpson’s biplane mode but the difference was insignificant. Conclusion: We concluded in this study use of these three techniques for LVEF was highly useful to diagnose accuracy but global longitudinal strain was showed better accuracy than that of simpson’s biplane mode and M-mode echocardiography. Keywords: Chest Pain, LVEF, global longitudinal strain, M-mode echocardiography, Simpson’s biplane mode, Accuracy